2014
DOI: 10.1371/journal.pone.0104777
|View full text |Cite
|
Sign up to set email alerts
|

Operational Momentum in Multiplication and Division?

Abstract: Biases are commonly seen in numerical cognition. The operational momentum (OM) effect shows that responses to addition and subtraction problems are biased in the whole-number direction of the operation. It is not known if this bias exists for other arithmetic operations. To determine whether OM exists in scalar operations, we measured response bias in adults performing symbolic (Arabic digits) and non-symbolic (dots) multiplication and division problems. After seeing two operands, with either a multiplication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 42 publications
2
45
1
Order By: Relevance
“…Only division, which was underestimated, showed a response bias significantly different from zero. In sum, we replicated the results from Katz and Knops (2014), showing a significant OM-effect for non-symbolic multiplication and division but no OM-effect for symbolic operations, despite having encouraged approximate calculation by omitting the correct response from the symbolic response alternatives. …”
supporting
confidence: 67%
See 3 more Smart Citations
“…Only division, which was underestimated, showed a response bias significantly different from zero. In sum, we replicated the results from Katz and Knops (2014), showing a significant OM-effect for non-symbolic multiplication and division but no OM-effect for symbolic operations, despite having encouraged approximate calculation by omitting the correct response from the symbolic response alternatives. …”
supporting
confidence: 67%
“…If participants responded non-randomly, then range and rank should have a significant effect on response choice (Katz & Knops, 2014). Indeed, we found that rank and range interacted for both multiplication and division in both symbolic and non-symbolic notation.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Support for this account has come from the influence of numbers on shifts of spatial attention (e.g., Fischer, Castel, Dodd, & Pratt, 2003); from identifying common brain parietal structures that are involved in addition and subtraction, as well as in directed saccadic eye movements (Knops, Thirion, Hubbard, Michel, & Dehaene, 2009); from observing OM in eye-fixation behavior (Klein et al, 2014); and from linking OM with attentional control measures (Knops et al, 2013). In comparison to this impressive support, the "compression account" of OM (McCrink et al, 2007; see also Chen & Verguts, 2012), which postulates that participants apply a linear transformation on the compressed mental number line representation, which in turn leads to over-or underestimating the outcome, has received less empirical support (Knops, Dehaene, Berteletti, & Zorzi, 2014;Knops et al, 2013; see also Katz & Knops, 2014).…”
Section: Discussionmentioning
confidence: 99%